Weight loss maintenance with exercise and liraglutide improves glucose tolerance, glucagon response, and beta cell function. Issue 4 (21st March 2023) - Jensen, Simon B. K.; Juhl, Christian R.; Janus, Charlotte; Lundgren, Julie R.; Martinussen, Christoffer; Wiingaard, Christoffer; Knudsen, Cecilie; Frikke‐Schmidt, Ruth; Stallknecht, Bente M.; Holst, Jens J.; Madsbad, Sten; Torekov, Signe S.
Abstract: Objective: The aim of this study was to investigate glucose tolerance, glucagon response, and beta cell function during a 1‐year maintenance period with either exercise, the glucagon‐like peptide‐1 receptor agonist liraglutide, or the combination after diet‐induced weight loss. Methods: In this randomized placebo‐controlled trial, adults with obesity (BMI: 32–43 kg/m 2 ) without diabetes underwent an 8‐week low‐calorie diet (800 kcal/d) and were randomized to 52 weeks of aerobic exercise, liraglutide 3.0 mg/d, exercise and liraglutide combined, or placebo. Change in glucose and glucagon response to a 3‐hour mixed meal test and disposition index, as a measure of beta cell function, were measured. Results: A total of 195 participants were randomized. After 1 year of treatment, the combination group had decreased postprandial glucose response by −9% (95% CI: −14% to −3%; p  = 0.002), improved beta cell function by 49% (95% CI: 16% to 93%; p  = 0.002), and decreased glucagon response by −18% (95% CI: −34% to −3%; p  = 0.024) compared with placebo. Compared with placebo, liraglutide alone improved postprandial glucose response by −7% (95% CI: −12% to −1%; p  = 0.018), but not beta cell function or glucagon. Exercise alone had similar postprandial glucose response, beta cell function, and glucagon response as placebo. Conclusions: Only the combination of exercise and liraglutide improved glucose tolerance, beta cell function, and glucagon responses after weight loss.